Research of the conditions of using an experimental method for carrying out quality control and quantitative evaluation of the stability of radio electronic means to the impact of powerful electromagnetic radiation - Fyk Оleksandr (Technology audit and production reserves, 2018)
The object of research is the REM functioning when it is irradiated with PEMI. One of the most problematic issues is the lack of a general methodology for quantifying the REM sustainability to the destructive effect of the intensity of the field of electromagnetic field. Therefore, this study is devoted to determining the conditions for the use of an experimental methodology for the quality control and quantitative assessment of the REM resistance to the PEMI action. In the course of the study, a technique was used that contains methods of theoretical generalization, analysis and synthesis, a method for representing nodes (parts) of REM using equivalent circuits, and a method for analyzing the stability of its nodes (parts, devices) separately. Modern REMs consist of many devices of various functional purposes. Each of the devices contains a large variety of links and elements. Therefore, the assessment of the REM sustainability by a block-by-block study of the stability of its nodes (parts, devices) will allow to evaluate the degree of PEMI impact on various nodes and the entire REM by separate parameters. In particular, the parameters characterizing the jamming environment created by the REM nodes, and the parameters characterizing the susceptibility degree of the various parts (nodes) of the REM to the effects of electromagnetic radiation. The applied nature of the proposed technique is the determination of the conditions for the use of various test methods related to the determination of the REM resistance to the PEMI impact, providing the following advantages: a higher degree of reliability of the results obtained in shorter periods of time; use of new, more noise-resistant types of communication between individual CME parts and the investigated REM when creating measurement stands. The research results allow to understand the order, the conditions of the experimental tests and the CME requirements. This will allow in subsequent studies to assess the stability of both a separate unit and the REM as a whole.